Transnational Solidarity in Times of Crises Citizen Organisations and Collective Learning in Europe - Lahusen, Christian; Zschache, Ulrike; Kousis, Maria (Palgrave Studies in European Political Sociology, 2021)
This open access collection is devoted to an in-depth, qualitative analysis of practices of cross-national solidarity in response to the current political and social crises, from citizens' initiatives to networks of cooperation among civil society actors. The book analyses existing informal groups at the grassroots, furthering transnational solidarity in three thematic areas: disability, unemployment and immigration. Contributions assess how civic groups respond to the various crises affecting Europe, especially the economic and refugee crises, presenting new findings from a systematic comparative study conducted in eight European countries (Denmark, France, Germany, Greece, Italy, Poland, Switzerland, and the UK). The research will be of interest to scholars, students, journalists, policy-makers and activists interested in civil society, social movements, charitable actions, altruism and solidarity, as well as European studies and the socio-economic challenges of current European crises.